2013
DOI: 10.7748/nop2013.03.25.2.32.e703
|View full text |Cite
|
Sign up to set email alerts
|

A palliative approach to care of residents with dementia

Abstract: Dementia is a progressive, life-limiting illness. People with the condition who move into a care home deserve palliative care. This article discusses an interprofessional pilot workshop for direct care providers held in a care home in British Columbia, Canada. The workshop aimed to incorporate a palliative approach into dementia care for residents. Workshop development, teaching strategies, evaluation and outcomes are shared. The four-hour workshop was structured to promote critical reflection and challenge pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…All six of the studies exploring sense of confidence as an outcome measure targeted staff understanding of dementia and BPSD as part of the intervention. Two papers found a significant increase in confidence following the intervention, one found no significant difference in confidence levels, one saw a decrease in confidence, and two did not statistically analyze their data …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…All six of the studies exploring sense of confidence as an outcome measure targeted staff understanding of dementia and BPSD as part of the intervention. Two papers found a significant increase in confidence following the intervention, one found no significant difference in confidence levels, one saw a decrease in confidence, and two did not statistically analyze their data …”
Section: Resultsmentioning
confidence: 97%
“…Both of the studies that did not statistically analyze their data found that staff reported their confidence to be higher following training . One study that focused on BPSD using a person‐centred approach also found improvements in communication and knowledge and understanding of dementia .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, one must take into account the possibility of undertreatment of pain and other symptoms in dementia . Even recognizing that an individual with dementia is in the dying phase has been shown to be difficult, leading to overly aggressive treatment instead of focusing on comfort . Specialized palliative care services have traditionally been devoted to individuals with cancer, and expanding these services to dementia and other diseases is now widely advocated because it is believed that these individuals also will benefit tremendously from it in terms of symptom management .…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Even recognizing that an individual with dementia is in the dying phase has been shown to be difficult, leading to overly aggressive treatment instead of focusing on comfort. 21,[34][35][36] Specialized palliative care services have traditionally been devoted to individuals with cancer, and expanding these services to dementia and other diseases is now widely advocated because it is believed that these individuals also will benefit tremendously from it in terms of symptom management. 8,21,30,31,34,35,37 Palliative care is not optimally developed for individuals with dementia, especially in care homes, which is where most individuals with dementia die.…”
Section: Discussionmentioning
confidence: 99%